Direct hactivism. (New Internationalist)
Focuses on the growing popularity of direct action through computer hacking around the world. Jose Ramos Horta's threat to the Indonesian Government; Increase in cyber crimes in the United States; International group of hackers' cyber attacks on the city of London in England.